ANALYSIS OF THE APPLICATION OF MURABAHAH CONTRACT TO IB GOLD OWNERSHIP PRODUCTS AT KB BANK SYARIAH SURABAYA - Afaf Fitriati; Mashudi Mashudi; Trischa Relanda Putra (Jesya, 2026)
This study examines the implementation of the murabahah contract in the iB Gold Ownership product at KB Bank Syariah KCP Surabaya. The research is motivated by the gap between administrative sharia compliance and substantive sharia compliance in murabahah-based gold financing, particularly regarding asset ownership, margin transparency, risk allocation, and contract validity. This study uses a descriptive qualitative approach, with data collected through interviews, observation, and documentation involving bank officers and customers. The findings show that the product demonstrates strong administrative compliance through the use of murabahah, disclosure of price and margin, fixed installment terms, and the integration of rahn as collateral. However, substantive compliance still requires stronger evidence of gold ownership by the bank before the sale contract, clearer documentation of ownership transfer, and better customer understanding of the distinction between murabahah margin and conventional interest. The contribution of this study lies in its analytical distinction between administrative compliance and substantive sharia compliance, offering a more critical framework for evaluating murabahah-based gold financing practices in Islamic banking.